PENGARUH BEBAN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA CV. DHARMAWAN GROUP KM 45 FARM BOGOR - Amelia Putri; Aprilia Astuti (Journal of Research and Publication Innovation, 2025)
The purpose of this study is to determine the influence of workload and job satisfaction on employee performance at CV Dharmawa Group k 45 farm in Bogor both partially and simultaneously. The method used in this study is quantitative. The sampling technique used saturated sampling and obtained a sample of 70 respondents. Data collection by distributing questionnaires to all respondents uses the likert scale as the measurement scale and SPSS Version 27 as the data processing application. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, determination coefficient and hypothesis test. The results of this study are that the workload does not have a significant effect on employee performance at CV Dharmawan Group KM 45 Farm Bogor, this can be proven from the simple linear regression equation Y = 53.662 – 0.665X1. The value of the coefficient of determining the influence contribution was 45.6% and the hypothesis test was obtained by calculating < ttable or (-7,550 < 1,995). Hypothesis test partially independent variables have no effect on dependent variables with H0 decision accepted and H1 rejected, meaning there is no significant influence. It is said to be significant because the probability value of significance is 0.001 < 0.05. Job satisfaction has a significant effect on employee performance at CV Dharmawan Group KM 45 Farm Bogor, this can be proven from the simple linear regression equation Y = 12.948 + 0.678X2. The value of the detrmination coefficient contributed to the effect of 62.1%. And the hypothesis test was obtained by counting > ttable or (10,561 > 1,955). Hypothesis test partially independent variables have an effect on dependent variables with H0 decision rejected and H2 accepted, meaning that there is a significant influence. It is said to be significant because the probability value of significance is 0.001 < 0.05. Workload and job satisfaction simultaneously have a significant effect on employee performance at CV Dharmawan Group KM 45 Farm Bogor, this can be proven from the regression equation Y = 25.884 – 0.303X1 + 0.516X2. The value of the determination coefficient is 68% while the remaining 32% is influenced by other factors. The hypothesis test obtained the value of F calculated > F table or (71.174 > 3.13). Simultaneous hypothesis testing of independent variables affects dependent variables with H0 decision rejected and H3 accepted, meaning that there is a significant influence. It is said to be significant because the significance probability value is 0.001 < 0.05.